Terapia fotodinâmica antimicrobiana como coadjuvante ao tratamento da doença periodontal: modelo experimental - Souza, Estefani Regina Leite Belinello de (2016)
Antimicrobial photodynamic therapy (aPDT) has been used as an adjuvant treatment for periodontitis. It combines a photosensitizer with a light source to induce reactive oxygen species and kill microbial cells. PpNetNI is a protoporphyrin derivated, and it has a chemical binding site at biofilm and great affinity to microbial cells. The aim of this study was to investigate the effects of aPDT as an adjuvant treatment for periodontitis. Thirty healthy male rats Wistar (Rattus norvegicus) were used in this study (Approved by UNINOVE Ethical committee AN0029/2015). Periodontitis was induced by placing a cotton ligature around the first mandibular molar in a subgengival position. The contralateral mandibular first molar received neither a ligature nor any treatment, and was used as a control. After 7 days, the ligature was removed and all animals received scaling and root planing (SRP) and were divided according to the following treatments: SRP group (received SRP and irrigation with PpNetNI, 10 µM) and PDT group (PpNetNI 10 µM followed by LED irradiation). PDT was performed with a LED (630 nm) with an output power of 400 mW (fluence-rate 200 mW/cm2; fluence 18 J/cm2). Rats were euthanized at 24 h, 48 h and 7 days postoperatively. The area of bone loss in vestibular region of the first molar was evaluated by Optical Coherence Tomography (OCT). Data were analyzed statistically (ANOVA and Tukey tests, p˂0.05). Inflammatory markers IL-1, IL-6 and IL-10 were also evaluated. The animals treated by aPDT showed bone gain of approximately 30% compared to the SRP group following 7 days from the treatment. PDT reduced periodontal tissue destruction and may be useful as an adjuvant to SRP in the treatment of periodontitis.